Representation of Verbal Mood in the Introduction of Shahnameh of Abu Mansouri: Comparison of Traditional Approach and Functional Theory on the Mood - Pooneh Abedin; Mohammad Dabirmoghadam (̒Ilm-i Zabān, 2022)
Mood in a general sense, is the way the speaker utters and expresses the meaning of the sentence and illustrates how the event has occurred from the speaker's perspective. There are tools for expressing Mood in all languages of the world, including verbal mood, modal verbs, modal adverbs, and adjectives. Among the means of expressing the mood, the verbal mood is of particular importance because in expressing the concept of a proposition the burden is on the main verb. In this paper, the representation of verbal mood in the introduction to Abu Mansouri's Shahnameh is studied within the comments and Segmentation of Khanlari (1353 Volume II) and Halliday's Functional Grammar theoretical foundations (Halliday and Matthiessen 2014). This study shows that, despite the distinction between the two approaches, the verbal mood is represented through the verbal stem, based on tense (past and present) and the elements used in verb inflection (pre and post-verb elements). The differences between the two approaches will also be expressed in terms of the representation of Mood in Persian, including incompatibility in the non-indicative mood (subjunctive and injunctive) subscale.